Disaster Risk Perception and Preparedness: a Cross-Sectional Study of Senior High School Student - Mubaroq, Bagja Al; Kosasih, Cecep Eli; Rosidin, Udin (Universitas Malahayati, 2025)
ABSTRACT Earthquakes are unpredictable, making disaster preparedness essential. Risk perception is key, but its relationship with preparedness remains inconsistent. To analyze the relationship between risk perception and disaster preparedness. A cross-sectional study with 73 high school students selected via accidental sampling from a population of 1,509. Risk perception was measured using PRISM (S-CVI/ave = 0.9; reliability r = 0.95, p < 0.001), and preparedness using LIPI/UNESCO-ISDR (validity 0.566–0.895; reliability 0.969). Data were analyzed using descriptive statistics and Pearson correlation. Most students had low-risk perceptions (50.7%) but were categorized as prepared (64.4%). No significant correlation was found (p = 0.1, r = -0.19). Disaster knowledge significantly influenced preparedness (p < 0.05). Disaster knowledge affects preparedness more than risk perception. Schools should integrate disaster education into curricula, collaborate with BPBD, and empower extracurricular programs like PMR and Scouts. Keywords: Earthquake, Preparedness, Risk Perception, Students